2010
DOI: 10.1108/09696471011059796
|View full text |Cite
|
Sign up to set email alerts
|

Co‐creating learning: insights from complexity theory

Abstract: PurposeRecent advances in the interactive technologies have transformed the way today's organizations and their different stakeholders learn. Now, because of the increasing learning requirements, neither these organizations nor their stakeholders can afford to be too self‐focused while learning; instead, they collaborate and learn together. Existing theories of learning are not sufficient to explain this complex learning “co‐creation”. Therefore, this paper aims to explore how different actors of a value netwo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 44 publications
1
30
0
1
Order By: Relevance
“…Ordanini and Parasuraman (2011) found that greater collaboration with customers leads to greater volume of innovation in NSD programs, but did not improve the radicalness of the innovations. However, the work of Desai (2010) suggests that the complexity theory might explain why prior research has found no direct effect of customer co-creation on radicalness of service innovations. NSD is a value network, and greater interaction of resources leads to adaptation of the perspectives of diverse actors and ultimately to new concepts, learning and more complex knowledge.…”
Section: Process Complexitymentioning
confidence: 99%
See 1 more Smart Citation
“…Ordanini and Parasuraman (2011) found that greater collaboration with customers leads to greater volume of innovation in NSD programs, but did not improve the radicalness of the innovations. However, the work of Desai (2010) suggests that the complexity theory might explain why prior research has found no direct effect of customer co-creation on radicalness of service innovations. NSD is a value network, and greater interaction of resources leads to adaptation of the perspectives of diverse actors and ultimately to new concepts, learning and more complex knowledge.…”
Section: Process Complexitymentioning
confidence: 99%
“…David Kelly, founder of IDEO, a leading design firm and developer of many radically innovative products and services, has suggested that a firm needs to come up with a lot of ideas to find the one concept that leads to the successful radical innovation. Complexity theory applied to learning co-creation (Desai, 2010) suggests that the synergies of a complex adaptive system generate more ideas and yield more creative solutions. Higher levels of NSD process complexity have the characteristics of a complex adaptive system, and the synergistic interactions of the diverse operant resources in the development process produce more radically innovative services.…”
Section: Theoretical Implications -Was Steve Jobs Wrong?mentioning
confidence: 99%
“…O conceito de cocriação aparece em vários contextos orientada a empresa, como virtual (Fuller, 2010), aprendizagem (Desai, 2010), desenvolvimento de produtos e inovação (Ramaswamy, 2011;Rowley et al, 2007).…”
Section: A Influência Da Cultura Organizacional Na Cocriaçãounclassified
“…Especially due to the given flexibility, every actor can be easily replaced. Therefore it will become important that those technological relationships reflect the relational type of leadership and are based on a many-to-many (m:n) logic (Desai, 2010).…”
Section: Conceptual Designmentioning
confidence: 99%